IMPLEMENTASI DATA MINING ALGORITMA APRIORI PADA APLIKASI TRANSAKSI PENJUALAN PT. ALFIR UNTUK MENENTUKAN POSISI PENYIMPANAN BARANG - Tri Ramdhany (Cloud Information, 2019)
PT. Alfir Berkah Abadi is a trading company that sells stainless pipes, there are various kinds of stainless pipes available at PT. Alfir. The stainless-stainless are distinguished by size, thickness and brand. In the process of storing goods, PT. Alfir keeps the pipe in a rack in a warehouse. But the number of slots in the rack does not match the number of types of stainless pipes so in 1 rack slot the number of different types of pipes and mixed up this can complicate the safety of the warehouse in the search for goods, so PT. Alfir needs information to determine the types of pipes in 1 rack slot correctly to facilitate the search. In carrying out its business processes PT. Alfir has used computer equipment to store and process transaction data. Transaction data can be used by using data mining to provide information for consideration in making decisions in determining the position of storage of goods. This application uses the Apriori algorithm to analyze sales transaction data at PT. Alfir. From the results of the analysis of the sales transaction data is processed so as to produce an intemet and ultimately produce the Association Rules and the results in the form of reports. This application was built using web-based programming and MySQL database. By using this application, gathering the results that can be obtained from the relationship between what goods are often received by consumers at PT. Alfir which can be used as information for companies to assist in the procurement planning and storage position of stainless pipes.